2011
DOI: 10.1186/1471-244x-11-27
|View full text |Cite
|
Sign up to set email alerts
|

Association of depression with treatment outcomes in Type 2 Diabetes Mellitus: A cross-sectional study from Karachi, Pakistan

Abstract: BackgroundTo assess the associations of depression with glycemic control and compliance to self-care activities in adult patients with Type 2 Diabetes MellitusMethodsThis cross-sectional study was conducted at a tertiary-care hospital in Karachi (Aga Khan University Hospital). Equal numbers of depressed and non-depressed patients were consecutively recruited from the diabetic clinic. Information on demographic and clinical characteristics was collected in face-to-face interviews and from medical records. Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 28 publications
3
32
2
2
Order By: Relevance
“…[91213] This association was not revealed in our patients; obviously this was related to anorexia originated by depression. This explains the higher rate of physical activity in T2D-depressed patients reported in literature;[914] however, this association was not revealed in our patients.…”
Section: Discussionmentioning
confidence: 72%
“…[91213] This association was not revealed in our patients; obviously this was related to anorexia originated by depression. This explains the higher rate of physical activity in T2D-depressed patients reported in literature;[914] however, this association was not revealed in our patients.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to previous studies, and in agreement with others, the current study revealed that women had a worse HRQoL than men patients with type 2 diabetes. This difference could be explained by the fact that women have a higher risk of developing cardiovascular disease and depression or anxiety than men. Furthermore, in addition to having greater difficulty in engaging in physical exercise, women usually find themselves overburdened with commitments toward household activities which may lead to a negative physical and psychological impact …”
Section: Discussionmentioning
confidence: 99%
“…There was difference of post prandial glucose between two groups, that was significant higher in case groups (304 vs. 208, p=0.02). This is relevant with previous study which stated depression complicate blood glucose control in metabolic syndrome or diabetes patient 3,4,5,25,26 . There was no correlation between metabolic syndrome component and depression.…”
Section: Introductionmentioning
confidence: 68%
“…About 15% population ever had major depression episode in their life and Note: *significant; Education 1: no education andelementary school, 2: junior and senior high school, bachelor, 3: graduate and post graduate; Occupation 1: Unemployed,house wife, 2: Private, labor, farmer 3: government employment, retired, army, policeman,Income 1:<1 million/month, 2:1-5 million/month, 3:>5 million/month, Marital Status 1: Never married, 2: married, 3: divorce/death spouse 3,4,5 . Depression decreased quality of life 6,7 .…”
Section: Introductionmentioning
confidence: 99%